Comparison of various capillary electrophoretic approaches for the study of drug-protein interaction with emphasis on minimal consumption of protein sample and possibility of automation - Michalcová, Lenka; Glatz, Zdeněk (Journal of separation science, 2015)
The binding ability of a drug to plasma proteins influences the pharmacokinetics of a drug. As a result, it is a very important issue in new drug development. In this study, affinity capillary electrophoresis, capillary electrophoresis with frontal analysis, and Hummel Dreyer methods with internal and external calibration were used to study the affinity between bovine serum albumin and salicylic acid. The binding constant was measured by all these approaches including the equilibrium dialysis, which is considered to be a reference method. The comparison of results and other considerations showed the best electrophoretic approach to be capillary electrophoresis‐frontal analysis, which is characterized by the high sample throughput with the possibility of automation, very small quantities of biomacromolecules, simplicity, and a short analysis time. The mechanism of complex formation was then examined by capillary electrophoresis with frontal analysis. The binding parameters were determined and the corresponding thermodynamic parameters such as Gibbs free energy ΔG0, enthalpy ΔH0, and entropy changes ΔS0 at various temperatures were calculated. The results showed that the binding of bovine serum albumin and salicylic acid was spontaneous, and that hydrogen bonding and van der Waals forces played a major role in the formation of the complex.